2012
DOI: 10.1155/2012/423905
|View full text |Cite
|
Sign up to set email alerts
|

Facing Your Fears in Adolescence: Cognitive-Behavioral Therapy for High-Functioning Autism Spectrum Disorders and Anxiety

Abstract: Adolescents with high-functioning autism spectrum disorders (ASDs) are at high risk for developing psychiatric symptoms, with anxiety disorders among the most commonly cooccurring. Cognitive behavior therapies (CBTs) are considered the best practice for treating anxiety in the general population. Modified CBT approaches for youth with high-functioning ASD and anxiety have resulted in significant reductions in anxiety following intervention. The purpose of the present study was to develop an intervention for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 54 publications
0
58
0
1
Order By: Relevance
“…At this stage, a further 27 studies were excluded from the final review of data for the following reasons. Eight studies were reports of secondary data (Boyd et al 2012;King and Desaulnier 2011;Lang et al 2010;Langdon et al 2013;Reaven 2009, 2011, Reaven et al 2009Rotheram-Fuller and MacMullen 2011;Scattone and Mong 2013), one study (Sze and Wood 2008) was a duplicate that had not been previously filtered out, one (White et al 2013) reported a non-significant effect of the intervention, five studies reported the effects of CBT for core features of ASD rather than mental health symptoms (Drahota et al 2011;Kenworthy et al 2014;Scarpa and Reyes 2011;Wood et al 2009aWood et al , b, 2014 and 12 included (n = 1) designs (Cook et al 1993;Lehmkuhl et al 2008;Nadeau et al 2014;Reaven and Hepburn 2003;Schleismann and Gillis 2011;Wood 2007, 2008) or did not have a comparator group (Reaven et al 2012b;Ooi et al 2008;Ozsivadjian and Knott 2011;White et al 2010;White et al 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, a further 27 studies were excluded from the final review of data for the following reasons. Eight studies were reports of secondary data (Boyd et al 2012;King and Desaulnier 2011;Lang et al 2010;Langdon et al 2013;Reaven 2009, 2011, Reaven et al 2009Rotheram-Fuller and MacMullen 2011;Scattone and Mong 2013), one study (Sze and Wood 2008) was a duplicate that had not been previously filtered out, one (White et al 2013) reported a non-significant effect of the intervention, five studies reported the effects of CBT for core features of ASD rather than mental health symptoms (Drahota et al 2011;Kenworthy et al 2014;Scarpa and Reyes 2011;Wood et al 2009aWood et al , b, 2014 and 12 included (n = 1) designs (Cook et al 1993;Lehmkuhl et al 2008;Nadeau et al 2014;Reaven and Hepburn 2003;Schleismann and Gillis 2011;Wood 2007, 2008) or did not have a comparator group (Reaven et al 2012b;Ooi et al 2008;Ozsivadjian and Knott 2011;White et al 2010;White et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies reviewed included children, but Reaven et al (2012b) distinguish the developmental needs of adolescents from children and developed the Facing your Fears Adolescent programme to meet those needs accordingly. For example, the parent component focuses on features of the parent-teen relationship relevant to navigating the transition through adolescence, and iPads are used to convey concepts of therapy and encourage home practice in a way that is accessible to typical adolescent functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The school-aged cohort included 10 families of children between the ages of 7 and 14 years ( M = 10.4 years, SD = 2.2) who participated in a randomized controlled trial of Facing Your Fears: Group Therapy for Managing Anxiety in Children with High-Functioning Autism Spectrum Disorders (FYF) (see Reaven, Blakeley-Smith, Nichols & Hepburn, 2011). The adolescent cohort included 21 families of teens between the ages of 13 and 18 ( M = 15.5 years, SD = 1.3) who were involved in the adolescent adaptation of the intervention (see Reaven, Blakeley-Smith, Leuthe, Moody & Hepburn, 2012b). The total sample comprised 31 youth ( M age = 13.8 years, SD = 3.0) with ASD and anxiety and their parents ( M age = 44.4 years, SD = 9.1).…”
Section: Methodsmentioning
confidence: 99%
“…Clarke and colleagues, and Kovshoff and colleagues, present promising results of randomized controlled trials of Attwood's (2004) Exploring Feelings schoolbased cognitive behavioural therapy (CBT) for anxiety in autistic children. Drmic and colleagues present similarly promising results for a school-based adaptation of the Facing Your Fears (Reaven et al 2012) intervention for autistic adolescents.. Maddox et al present impactful research on the durability of CBT over time, as well as predictive concomitants. Moskowitz and colleagues present a multiple baseline trial of a positive behaviour and CBT intervention for anxiety in autistic children with ID, showing promising results on both behavioural and psychophysiological measures.…”
Section: Mechanisms Measurement and Application To Treatment: The Smentioning
confidence: 97%